The Optimization of the Number of Halal Auditor to Improve Halal Product Assurance in Indonesia (The Perspective of Law Number 33 of 2014 concerning Halal Product Guarantee) - Farid Wajdi; Cynthia Hadita (RIRAI Publisher, 2021)
The lack of quantity of halal auditors has implications for the less than optimal implementation of halal product guarantee in Indonesia, so it is necessary to compare with Brunei Darussalam in standardizing halal auditors. The research method used in this research is normative juridical. The results of the study indicate that halal auditors still need to optimize the quantity of halal auditors so that they are more optimal in halal and there will be an increase in halal product guarantee in Indonesia. Comparative with Brunei Darussalam, apart from an adequate quantity of halal auditors, there is also a code of ethics for trainee auditors (halal auditors), Indonesia needs to optimize the number of halal auditors and also have a code of ethics for halal auditors. So the results are more optimal and in accordance with Law of the Republic of Indonesia Number 33 Year 2014 on Halal Product Guarantee.